2002
DOI: 10.1089/105072502761016467
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the Risk of Relapse After Withdrawal of Medical Therapy for Graves' Disease

Abstract: It has been a continuing challenge to try and identify those patients with hyperthyroid Graves' disease likely to remain in remission after an antithyroid drug course or to manage the medical treatment so as to increase the chance of remission. On average, the overall relapse rate is approximately 50% and any significant reduction of this figure would be of practical as well as theoretical value. The numerous controlled prospective studies performed in many parts of the world, with varying iodine intakes, have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
4
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 20 publications
0
29
4
6
Order By: Relevance
“…On the contrary, Vitti et al reported that the relapse rate of Graves' disease with ophthalmopathy was higher than that of Graves' disease without ophthalmopathy (71.9% vs 57.8%; p = 0.08) [24]. Although the presence of ophthalmopathy is a possible high risk factor of relapse, it has a low predictive value alone [25]. In our study, the remission rate of Graves' disease in the 2 groups was not significantly different.…”
Section: Discussioncontrasting
confidence: 80%
“…On the contrary, Vitti et al reported that the relapse rate of Graves' disease with ophthalmopathy was higher than that of Graves' disease without ophthalmopathy (71.9% vs 57.8%; p = 0.08) [24]. Although the presence of ophthalmopathy is a possible high risk factor of relapse, it has a low predictive value alone [25]. In our study, the remission rate of Graves' disease in the 2 groups was not significantly different.…”
Section: Discussioncontrasting
confidence: 80%
“…Conservative therapy with ATD is the first choice treatment in Europe and it is proven to be effective in achieving euthyroidism in Graves' patients [3], even if long-term remission after therapy withdrawal is unsatisfying with relapse rates of 30-50% [9,[16][17][18][19][20]. However, if the great rate of relapse(s) may be related to TRAb levels and/or other parameters, such as gender, age, fT4 levels or goiter size is still controversial [13,14,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The association between smoking and Graves' disease is further underscored by the fact that smoking increases the risk for a relapse of Graves' hyperthyroidism (103,104). Smoking also increases the chances of an exacerbation of the eye disease after treatment with 131 I, and it reduces the efficacy of radiotherapy and corticosteroid treatment of the ophthalmopathy (105,106).…”
Section: Smokingmentioning
confidence: 99%